Design of a Non-isolated Single Phase Online UPS Topology with Parallel Battery Bank for Low Power Applications - Aamir, Muhammad (Springer Theses, Recognizing Outstanding Ph.D. Research, 2019)
XXIII, 108 p. 78 illus., 39 illus. in color.